STRATEGI VALUE CHAIN ANALYSIS BAGI PENINGKATAN DAYA SAING INDUSTRI KECIL DI INDONESIA (Fokus Ekonomi, 2010)
Small scalled industries is the one of the actors who plays an important role in Indonesian economic development. Their existence will become more important for their great contribution to the national income and expand the employment of opportunities. Based on this important role, the empowerment of the small scaled industries have to get serious attention. Value Chain is a powerfull analysis tool which can be used to identify the key activities within the firm which form the value chain for the firm and have the potential of a suistainable competitive advantage. The competitive advantage of the firm lies in its ability to perform crucial activities along the value chain better than its competitor. The aim of the value chain is to maximize value of the customer while minimizing costs.